Impact of perceived environmental legacy on residents’ pro-environmental behaviors in large-scale sport events: a moderation analysis of authenticity - Chen, Jiexin; Wu, Ji; Wu, Yigang (Frontiers in Sports and Active Living, 2025)
IntroductionPrior research has demonstrated that residents' perceptions of environmental legacy (PEL) following large-scale events yield several positive outcomes, such as subjective well-being and support of future events. However, the role of PEL in shaping residents' pro-environmental behaviors (PEBs) remains underexplored. Drawing on the Norm Activation Model, this study investigated how PEL is associated with PEBs through the mediation of perceived fit (PFT) and the moderation of authenticity evaluation (AUTH).MethodsData were collected via an online survey administered to 823 residents of Hangzhou, one year after the 2023 Hangzhou Asian Games. Structural equation modeling revealed that PFT fully mediated the relationship between PEL and PEBs.ResultsLatent moderated structural modeling showed that AUTH strengthened the direct relationship between PEL and PEBs.DiscussionThe study advances event legacy literature by identifying the psychological pathways associated with the activation of PEBs, which are mediated by PFT and moderated by AUTH. For policymakers and event organizers, the findings underscore the importance of designing environmental legacies that are both authentic and culturally resonant to maximize long-term behavioral impacts. To enhance residents' PEBs, stakeholders in large-scale sports events should prioritize the authenticity and value-fit of their environmental strategies.